2005
DOI: 10.1519/r-14353.1
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic and Resistance Exercise Sequence Affects Excess Postexercise Oxygen Consumption

Abstract: Excess postexercise oxygen consumption (EPOC) may describe the impact of previous exercise on energy metabolism. Ten males completed Resistance Only, Run Only, Resistance-Run, and Run-Resistance experimental conditions. Resistance exercise consisted of 7 lifts. Running consisted of 25 minutes of treadmill exercise. Vo(2) was determined during treadmill exercise and after each exercise treatment. Our findings indicated that treadmill exercise Vo(2) was significantly higher for Resistance-Run compared with Run-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
3
22

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(76 citation statements)
references
References 0 publications
4
47
3
22
Order By: Relevance
“…Além disso, poucos estudos analisaram os efeitos da ordem de execução sobre o consumo de oxigênio (9,10,20) . Por exemplo, Palmer e Sleivert (21) verificaram que .…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Além disso, poucos estudos analisaram os efeitos da ordem de execução sobre o consumo de oxigênio (9,10,20) . Por exemplo, Palmer e Sleivert (21) verificaram que .…”
Section: Discussionunclassified
“…VO 2 era mais elevado no exercício aeróbio realizado uma e oito horas após o exercício de força em relação à mesma situação sem esforço prévio. Drummond et al (10) também evidenciaram aumento do . VO 2 , da FC e da percepção subjetiva do esforço durante a realização do exercício aeróbio em três períodos de tempo (10, 20 e 25 minutos) da ordem FA quando comparado com a ordem AF, contrapondo aos resultados encontrados por nosso estudo.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…However, conventional exercise intensity, volume, frequency, repetition, velocity, and rest intervals were commonly different for aerobic and resistance exercise. Drummond et al (2005) found that the aerobic-first sequence was more effective in augmenting excess post-exercise oxygen consumption. In their study, the aerobic exercise involved continuous running at a pace that corresponded to 70% V 4 O 2peak for 25 min, whereas resistance exercise consisted of three sets of 10 repetitions at 70% of 1-repetition maximum (RM).…”
Section: Introductionmentioning
confidence: 94%